Pilotis tropical: a habitação aérea na arquitetura moderna brasileira - Manuella Mendonça Pinheiro Pamponet (2024)
The concept of pilotis, introduced in the early 20th century by Le Corbusier as one of the five points of the new architecture, was presented to Brazilian architects as a new constructive, spatial, and plastic possibility. Considering how the origin of the pilotis occurred in Corbusier's work and how this architectural device was later absorbed and widely incorporated in Brazil, this dissertation proposes to catalog and analyze 80 examples of residential Brazilian pilotis. The analysis was guided by two main points: materiality (constructional finishes and techniques) and the motif (which sought to understand the motivations, justifications and particularities of the use of pilotis in each of the projects). The results, which sought to classify the projects by their similarities, revealed five categories: the observatory pilotis, aerial pilotis, porch pilotis, service pilotis, and the square pilotis. Finally, we seek to investigate aspects of the native condition of modern Brazilian architecture, to evidence that there was an authentic aerial housing production in Brazil, the tropical pilotis.